Intrahousehold empowerment gaps in agriculture and children's well-being in Bangladesh - Malapit, Hazel J.; Sraboni, Esha; Quisumbing, Agnes R.; Ahmed, Akhter (John Wiley & Sons, 2019)
This article examines the relationship between empowerment gaps between spouses and children's nutritional status and education using nationally representative data from the 2012 Bangladesh Integrated Household Survey. We measure relative empowerment of spouses using the recently developed Women's Empowerment in Agriculture Index. We find that while gender gaps in empowerment are only linked weakly to children's nutritional status, fathers’ and mothers’ empowerment have different effects on investment in children. Fathers’ empowerment is positively associated with younger children's nutrition and schooling, while mothers’ empowerment is more important for girls’ education in general and in keeping older boys and girls in school.